Lotus Bioactive-Loaded Carboxymethyl Cellulose Films for Shrimp Preservation - J K Pallavi; P Hema Harshitha; N V Kanimozhi; M Sukumar (Journal of Multidisciplinary Applied Natural Science, 2026)
Shrimp is highly susceptible to microbial spoilage, creating a need for sustainable antimicrobial packaging systems. In the present study, a biodegradable carboxymethyl cellulose (CMC)-based composite film incorporating lotus-derived flavonoids, essential oil, and carbon nanoparticles (CNPs) was developed for shrimp preservation. A Box–Behnken design was employed to optimize film composition, resulting in a minimum film formation time of 28.2 ± 0.2 h at 0.4% essential oil, 1.65% flavonoids, and 1.2% CNPs. The films were prepared by solution casting and characterized for physicochemical, mechanical, antioxidant, antimicrobial, and biodegradability properties. The optimized film exhibited good structural integrity, a maximum tensile force of 10.5 N, moderate water vapor barrier properties, strong antioxidant activity, and rapid biodegradability under soil conditions. Shelf-life evaluation of Litopenaeus vannamei stored at 16–18 °C demonstrated maintenance of acceptable pH, total phenolic content, and total volatile base nitrogen levels over 15 days. A modified Kaplan–Meier approach further indicated delayed microbial spoilage in shrimp packaged with the composite film compared to conventional plastic packaging, although the differences were not statistically significant at the 95% confidence level. The results suggest that lotus bioactive-loaded CMC films have potential as sustainable active packaging materials for seafood preservation.